2021
DOI: 10.1080/21655979.2021.1945522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential targets of triptolide in regulating the tumor microenvironment of stomach adenocarcinoma patients using bioinformatics

Abstract: This study aimed to identify potential pharmacological targets of triptolide regulating the tumor microenvironment (TME) of stomach adenocarcinoma (STAD) patients. A total of 343 STAD cases from The Cancer Genome Atlas (TCGA) were assigned into high-or low-score groups applying Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data (ESTIMATE). Hub genes were identified from differentially expressed genes (DEGs) shared by stromal-and immune-related components in the TME of STAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Solute carrier family 12 member 8 has been reported to be upregulated in bladder cancer and related to patient prognosis and tumor immune cell infiltration [ 83 ]. C-X-C chemokine receptor type 4 was identified as a therapeutic target of triptolide in the treatment of STAD patients by modulating the TME [ 84 ]. Domain-containing protein 1 has been reported upregulated in most cancers and played oncogenic roles in pan-cancer by comprehensive bioinformatic analysis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solute carrier family 12 member 8 has been reported to be upregulated in bladder cancer and related to patient prognosis and tumor immune cell infiltration [ 83 ]. C-X-C chemokine receptor type 4 was identified as a therapeutic target of triptolide in the treatment of STAD patients by modulating the TME [ 84 ]. Domain-containing protein 1 has been reported upregulated in most cancers and played oncogenic roles in pan-cancer by comprehensive bioinformatic analysis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified several cancer-related significantly enriched signaling pathways, mainly including ECM interaction and repair of genetic alteration, which are related to high NUDT10 expression in GC. The ECM is an important component of the tumor microenvironment and plays a key role in tumor progression and patient survival [ 25 ]. Zhou L, et al constructed a novel prognostic signature for GC based on large sequencing data and showed that ECM-receptor interaction is an important platform for the function of prognosis-related differentially expressed genes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standardized proteins and ligands were imported into AutoDockTools (version 1.5.6) and converted into a PDBQT format. Using the AutoDock Vina software (version 1.1.2), we ran a program for molecular docking using docking parameters; the complex conformation with the minimum binding energy and highest binding affinity for each molecule was selected for further analysis [ 24 ]. Generally, the binding energy < 0 kcal/mol indicates that the ligand can bind to the receptor protein, while the binding energy ≤ −5.0 kcal/mol reveals that the ligand and the protein have a good binding ability [ 25 ].…”
Section: Methodsmentioning
confidence: 99%